Fully measured plan of the Bisaldeo Temple by A.C.L. Carlleyle - Temples of India Project Team (Jio Institute, 2024)
In 1872, A.C.L. Carlleyle visited Bisalpur and provided the first known archaeological report on its temples under the supervision of Alexander Cunningham, the first Director General of the Archaeological Survey of India (ASI). His report includes a fully measured plan of the Bisaldeo Temple that was lithographed at the Surveyor General’s office in 1877.